Dual-aptamer-activated RCA-MOF synergistic platform for visual detection of leukemia-derived exosomes - Ying Shen; Yunlong Xiao; Lu Liu; Suzhen Zhai; Renwu Mu; Jiahui Chen; Xiaoyan Yang; Xiaojun Wen; Chunlin Zhang; Hai Shi (Analytica Chimica Acta, 2026)

Ultrasound-enhanced co-leaching of uranium and associated rare earth elements from coarse-grained uranium tailings using Fe2(SO4)3–H2SO4 - Jiahui Zeng; Chao Liu; Yuehui Ma; Mu Li; Xianping Luo; Xiaoyu Sun; Xuegang Wang; Zhanxue Sun; Zhiyuan Ma (Minerals Engineering, 2026)

Comparative Analysis of Growth Patterns and Sexual Dimorphism of Scylla paramamosain in Pond Culture - Jiahui Liu; Ronghua Li; Yang Jiang; Yun Hu; Zhuang Li; Qingyang Wu; Changkao Mu; Weiwei Song; Chunlin Wang; Ce Shi (Fishes, 2026)
To investigate the growth patterns and sexual differences in pond-cultured mud crabs (Scylla paramamosain), this study measured eight growth patterns in pond-cultured S. paramamosain aged 1 to 5 months, including internal carapace width (ICW), abdomen width (AW), body height (BH), carapace length (CL), propodus length (PL), merus length (ML), first periopod merus length (1PML), and body weight (BW), with measurements taken monthly. The growth patterns for females, males, and a mixed-sex group were fitted using the following three growth curve models: Logistic, Gompertz, and von Bertalanffy. The fitting results indicate that the optimal growth model for male S. paramamosain is the Logistic model, while the optimal growth model for female S. paramamosain is the von Bertalanffy model. The predicted growth inflection points and inflection weight for male S. paramamosain are 3.15 months and 155.00 g, respectively; for female S. paramamosain, the predicted growth inflection point and inflection weight are 4.25 months and 228.71 g, respectively; and for mixed-sex S. paramamosain, the growth inflection point and inflection weight are 3.22 months and 151.80 g, respectively. Males achieve a rapid growth period earlier (at 3–4 months of age) than females, with the weight of male crabs significantly greater than that of females at four months of age (p

Preferential flow reduces overland flow on slopes: insights from a field experiment on the Chinese Loess Plateau - Yongfu Wen; Chaojun Gu; Peng Gao; Jiahui Zhou; Xiaoxue Guo; Xingmin Mu; Xucheng Ai; Ruidun Zhang; Siyu Ren (Journal of Hydrology, 2026)

Characterization and Antigenicity of whey protein isolate gels modulated by cross-linking of cysteine synergized with transglutaminase: impacts of cysteine concentrations - Yifei Yan; Zhishen Mu; Jiahui Guo; Minghan Zhang; Juncai Hou; Zhanmei Jiang (International Dairy Journal, 2026)

Response of soil conservation functions to vegetation dynamics and restoration potential on the Loess Plateau - Xiaoxue Guo; Peng Tian; Guangju Zhao; Peng Gao; Chaohui Ma; Rui Shan; Jiahui Zhou; Xingmin Mu (CATENA, 2026)

Decoupling effects of driving factors on sediment load in the middle reaches of the Yellow River - Chaohui Ma; Xiaoxue Guo; Ruirui Xu; Peng Gao; Jiahui Zhou; Yuxuan Zhang; Xingmin Mu (CATENA, 2026)

Self-healing, highly stretchable, recyclable PU-curcumin elastomer with substrate-sensitive solid-state fluorescence - Linjie Wei; Xiubin Xu; Hongchun Mu; Wantong Lin; Jiahui Tang; Jieran Li; Jianwei Liu; Haitao Dong; Danfeng Yu; Xu Wu (Chemical Engineering Journal, 2025)

Transitions in slope runoff generation mechanisms induced by land use change in the Loess Plateau, China - Jiahui Zhou; Yongfu Wen; Peng Gao; Siyu Ren; Xiaoxue Guo; Xingmin Mu (CATENA, 2025)

Soil physicochemical properties and roots promoted preferential flow development after vegetation restoration - Yongfu Wen; Mengzhen Li; Peng Gao; Jiahui Zhou; Xucheng Ai; Yuxuan Zhang; Xingmin Mu (Journal of Hydrology, 2025)

Unraveling the main chemical mechanism of PM2.5 pollution caused by open burning of sugarcane straw during winter in southern China: The Pivotal Role of NOx and NH3 Oxidation-Neutralization - Xu Wei; Guiyun Liang; Jingying Mao; Junchao Yang; Yijun Mu; Chuan Nong; Dabiao Zhang; Jiahui Lu; Xishou Huang; Ying Wu; Zhaoyu Mo (Environmental Pollution, 2025)

Hybrid electrospun fibers with metal-based catalysts for zinc-air battery: Recent development and future perspectives - Mahmood ul Haq; Yongbiao Mu; Saz Muhammad; Baoxin Wu; Kejun Yan; Jiahui Luo; Zheng Li; Zhiqing Tang; Muhammad Ajmal; Wenjia Li; Lin Zeng (Chemical Engineering Journal, 2025)

Unveiling the Characteristics of Microbiota in Different Mucosal Layers of Leopard Coral Grouper (Plectropomus leopardus) - Jiahui Wang; Shengtao Gao; Zhenyuan Xu; Zhihui Yang; Qianqian Mu; Zijian Li; Pingping Liu; Jingjie Hu; Zhenmin Bao (Marine Biotechnology, 2025)

Self-gelated flexible lignin-based ionohydrogels for efficient self-powered strain sensors - Jiahui Mu; Cuihuan Li; Deqiang Li; Xianliang Song; Sheng Chen; Feng Xu (Chemical Engineering Journal, 2025)

Overcoming radiation-induced PD-L1 upregulation by novel gadolinium-palladium nanoplatforms for enhanced tumor radio-immunotherapy - Kai Guo; Hui Liu; Mengmeng Zhang; Nengyi Ni; Mengyao Mu; Ke Ren; Jiahui Chen; Qing Fan; Xueli Xu; Xiao Sun; Ximing Wang (Chemical Engineering Journal, 2025)

Cellulose-based colorimetric/ratiometric fluorescence sensor for visual detecting amines and anti-counterfeiting - Cuihuan Li; Yuan He; Jiankang Zhang; Jiahui Mu; Junya Wang; Mengyao Cao; Haq Nawaz; Sheng Chen; Feng Xu (Carbohydrate Polymers, 2024)

Structural characterisation and anti-colon cancer activity of an arabinogalactan RSA-1 from Raphani semen - Qi Li; Shuang Jiang; Qianbo Wang; Jiahui Sun; Zhibin Wang; Xiaotong Wang; Xuepeng Shi; Yuanqiu Mu; Lin Wei; Chunjuan Yang (Carbohydrate Polymers, 2024)

Mechanism of peroxymonosulfate activation by nanoparticle Co@N–C: Experimental investigation and theoretical calculation - Mu Li; Lin Lin; Wei Zhang; Yubin Zou; Jiahui Hu; Yin Li; Bing Li; Feiyun Sun; Xiao-yan Li (Chemosphere, 2024)

Coupling coordination relationships between air pollutant concentrations and emissions in China - Qian Wu; Song Hong; Lu Yang; Hang Mu; Chaoqing Huang; Xiaoxiao Niu; Yanmei Zhong; Jiahui Yi; Chao He (Atmospheric Pollution Research, 2023)